An Existential Approach to HIV Related Psychotherapy (Existential Analysis: Journal of the Society for Existential Analysis, 1996)
This paper outlines some of the issues that arise in the practice of psychotherapy when HIV is an issue. The paper argues that, due to the relational focus on the approach & the fundamental anxieties that arise in this area, the existential-phenomenological approach is particularly suited to assisting clients who face the challenges of life with HIV.